Climate change-induced stress in the honey bee Apis mellifera L.- a genetic review - Sagastume, Soledad; Cilia, Giovanni; Henriques, Dora; Yadró, Carlos; Corona, Miguel; Higes, Mariano; Pinto, M. Alice; Nanetti, Antonio; Martín-Hernández, Raquel (Frontiers in Physiology, 2025)
Climate change is a powerful driver of stress, as it reinforces hotter and drier environments. For bees, the most concerning aspects of these new environmental conditions are the resistance and resilience of bees to changes in temperature, humidity and ultraviolet radiation, as well as the negative effect on diversity of food resources which can lead in nutritional stress. The climatic vulnerability of various bee species and subspecies varies worldwide, as they experience varying levels of stress and display distinct behaviors, weaknesses, and lifespans. To understand these differences, it is crucial to consider both the genetics and epigenetics of bees, as these factors play a key role in their response, resistance, and adaptation to new stressors. This review provides a guide of genetic and epigenetic markers involved in the cellular response of Apis mellifera to most common stressors derived from climate change. Understanding how the various molecular mechanisms interact to restore homeostasis during the stress response is essential for designing future studies based on molecular markers.